Definition of The “Minister” in Government Regulation 11/2021 Concerning Village-Owned Enterprises - Saptono Jenar (Fakultas Hukum Universitas Lampung, 2022)
Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises (GR VOE) is one of the implementing regulations (verordnung or delegated laws and regulations) of Law Number 11 of 2020 concerning Job Creation (Job Creation Law). However, there is a different definition regarding the word